Empathy Crisis and Teacher Role Modeling: Adapting Bandura’s Theory for 21st-Century Character Education - Arum Nurul Aripin; Nanda Dwisetya; Viorrie Fitrah Azahra; Sitti Chadidjah (Institut Agama Islam Persis Bandung, 2025)
The digital transformation in the 21st century has triggered disruptions in social interactions, leading to a decline in empathy and a character crisis among Generation Z students. This article aims to examine the relevance of Albert Bandura's Social Learning Theory in mitigating the negative impacts of digital isolation and optimizing the formation of prosocial behavior. Employing a qualitative approach, this study analyzes the principles of observation, imitation, and modeling within the context of contemporary character education, particularly through the Mentor Life Learning framework at the primary school level. The analysis reveals that overreliance on gadgets without collaborative management fosters individualistic attitudes that threaten the humanizing essence of education. Therefore, the application of Bandura's theory requires educators to transform into